The Involvement of Third-Party Professionals in Business Registration and Property Transfer - Coste, Cyriane Marie (World Bank, Washington, DC, 2019)
Complex business regulations and bureaucratic processes tend to be obstacles for new entrepreneurs. To navigate these processes as smoothly as possible, entrepreneurs may solicit the services of third-party professionals. Whether in business incorporation or land transactions, third-party agents provide professional assistance and ensure that certain processes comply with the regulations in place. Depending on the economy and the specific regulatory process, these professionals can be lawyers, notaries or accountants, among others. This policy note explores the role of third-party professionals in the areas of starting a business and registering property in 168 economies and analyzes some of the differences in terms of time and costs for services provided by third-party professionals, as well as trends and reforms over time. The doing business indicator sets for these areas are used to benchmark the steps, cost, and time to incorporate a business and to transfer a property.